(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Mutual funds are one of the most widely recognized financial innovations in the world, By providing an opportunity for savers and small investors who do not have adequate financial resources or have insufficient experience or time to enter the security markets. The study began with a major problem: "How will mutual funds be reflected on the Saudi Stock Market Index?" Which included a range of intellectual and practical sub-questions because of the growing need for mutual funds that allow savers and investors to operate their funds in funds. To deal with securities within the financial market. The data of the private investment funds in the Kingdom of Saudi Arabia for the period 2000-2017 were analyzed in terms of relationship and impact on the market value index using the statistical program (SPSS.v25) and (Excel), The study reached a number of conclusions, the most important of which is the existence of a correlation relationship between the very strong and medium between the mutual funds and the market value index, as well as the existence of a relationship of significant statistical significance between them.